2007
DOI: 10.1089/scd.2007.0020
|View full text |Cite
|
Sign up to set email alerts
|

Blastocyst-Derived Trophoblast Stem Cells from the Rhesus Monkey

Abstract: Although trophoblast stem cells can be obtained directly from blastocyst outgrowths in the mouse, this has never been described in primates. In human and non-human primates, trophoblast cells have been obtained from embryonic stem (ES) cells or embryoid bodies (EBs). The results reported here show for the first time that cells with the characteristics of trophoblast stem cells can be derived directly from rhesus monkey blastocyst outgrowths. The cells expressed trophoblast markers and were maintained for multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 60 publications
2
43
3
Order By: Relevance
“…Bovine and porcine trophectoderm-derived stem cells also require feeder layers for maintenance, although in one report bovine TSC were maintained in the presence of fibroblast-conditioned medium alone (18). On the other hand, we found that rhesus trophectoderm-derived cells could be maintained in culture without feeder layers or the addition of BMP4 or FGFs (19).…”
Section: A Growth Factor Requirements Of Trophectoderm-derived Stem mentioning
confidence: 66%
See 1 more Smart Citation
“…Bovine and porcine trophectoderm-derived stem cells also require feeder layers for maintenance, although in one report bovine TSC were maintained in the presence of fibroblast-conditioned medium alone (18). On the other hand, we found that rhesus trophectoderm-derived cells could be maintained in culture without feeder layers or the addition of BMP4 or FGFs (19).…”
Section: A Growth Factor Requirements Of Trophectoderm-derived Stem mentioning
confidence: 66%
“…Isolation of trophectoderm-derived stem cells from primate embryos proved more difficult, and it is only recently that cells with TSC characteristics were obtained from rhesus blastocyst outgrowths plated on collagen-coated dishes after initial expansion with rhesus embryonic feeder cells (19). These cells were maintained as continuously replicating cultures in the absence of growth factors or feeder layers, distinguishing blastocyst-derived TSC in the mouse and the rhesus monkey.…”
Section: A Growth Factor Requirements Of Trophectoderm-derived Stem mentioning
confidence: 99%
“…However, TS lines that are independent of FGF signalling have also been established in rats as well as in another rodent, the common vole (Grigor'eva et al 2009, Chuykin et al 2010. A trophoblast cell line derived from rhesus monkey blastocysts was maintained independently of FGF signalling (Vandevoort et al 2007). Numerous stable trophoblast cell lines expressing trophoblast markers have been isolated from expanded cattle blastocysts (Talbot et al 2000, Shimada et al 2001.…”
Section: The Maintenance Phase Of Trophoblastsmentioning
confidence: 99%
“…Such TSC can be cultured in a continuously self-renewing state in vitro in the presence of FGF4 plus heparin, but also require NODAL signaling, which is usually derived from a supporting feeder layer of primary embryonic fibroblasts (Tanaka, Kunath et al 1998;Rossant 2001;Rossant 2007). However, it should be noted that dependency on FGF4 may not be a universal feature of TSC from all species (Vandevoort, Thirkill et al 2007;Grigor'eva, Shevchenko et al 2009). There have been many excellent reviews on embryonic and trophoblast stem cells (TSC), and the differences that distinguish them.…”
Section: Embryonic Stem Cells (Esc) and Trophoblast Stem Cells (Tsc)mentioning
confidence: 99%